2021
DOI: 10.1002/star.202100020
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction of Polyphenol from Panax Quinquefolius L. Using Central Composite Design/Response Surface Methodology

Abstract: Central composite design and response surface methodology are adopted to explore the extraction process of polyphenols from Panax quinquefolius L., including the extraction time, extraction temperature, ethanol concentration, and the influence of interaction effects, and establish the multiple regression model. The results show that the optimal extraction conditions for polyphenols of P. quinquefolius L. are 61 °C of extraction temperature, 38 min of extraction time, 48% of ethanol concentration and the polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The contents of (A) fourteen saponin and (B) nine polyphenols in SLPN and SLPN-instant beverage. The extraction condition of the present study is similar to that of the other study that polyphenols are extracted from P. quinquefolius L., and the extraction rate reached 48% (34). The interaction between (A) and (C) showed that when the ethanol concentration is 30-40%, material liquid ratio 1: 3A-D).…”
Section: Saponins and Polyphenols Affect The Antioxidant Activity Of ...supporting
confidence: 83%
“…The contents of (A) fourteen saponin and (B) nine polyphenols in SLPN and SLPN-instant beverage. The extraction condition of the present study is similar to that of the other study that polyphenols are extracted from P. quinquefolius L., and the extraction rate reached 48% (34). The interaction between (A) and (C) showed that when the ethanol concentration is 30-40%, material liquid ratio 1: 3A-D).…”
Section: Saponins and Polyphenols Affect The Antioxidant Activity Of ...supporting
confidence: 83%
“…At 60-70 • C, the extraction yield dropped due to the alteration of the polyphenols structure and their consequent inactivation. At 70-80 • C, the yield of polyphenols increased again, possibly due to the enhancement of some heat-sensitive polyphenols extraction [23]. Consequently, a temperature range of 50-70 • C is a suitable temperature for the PEIL extraction.…”
Section: Single-factor Experimental Analysismentioning
confidence: 99%
“…4b show the response surface and contour of TS% and biochar. The response surface changed greatly, and the contour was irregularly circular, indicating that there was a signi cant effect between TS and biochar (Zhu et al 2021). This might be due to the signi cant effect of high-order items in the regression model (p < 0.05).…”
Section: Interaction Effects Of Ts Biochar and Fe 3 O 4 On Ad Charact...mentioning
confidence: 99%
“…(1) was obtained as follows: greatly represents the relationship between predicted and observed value(Cheng et al 2022). The lack of t P-Value of the model was 0.0625 (P > 0.05), indicating that the regression model had a high degree of t and could be used to predict the response value(Zhu et al 2021). The P-Values of different factors were less than 0.05 except x 2 , x 1 x 2 , x 1 2 x 2 , showing that they performed a signi cant impact on methane yield.…”
mentioning
confidence: 96%